PENCEGAHAN STUNTING SEJAK DINI MELALUI OPTIMALISASI MODIFIKASI BAHAN PANGAN LOKAL DESA SEDAGARAN KECAMATAN SIDAYU KABUPATEN GRESIK - Ariestiningsih, Eka Srirahayu; Has, Dwi Faqihatus Syarifah; Kurniawan, Bhagaskoro Ardhianto; Rahma, Artiyas Maulina; Riswanto, Maulidya Fatikhaa Rizqi; Savitri, Silviana; Visyawaludina, Ruli Annisa (Mitra Mahajana: Jurnal Pengabdian Masyarakat, 2024)
Preventing stunting from an early age is an important thing that must be implemented immediately, considering that stunting is a problem faced by countries in the world, including Indonesia. The Indonesian government is very serious about accelerating the reduction in stunting rates by issuing Presidential Regulation Number 72 of 2021 and has received a positive response as evidenced by data from the 2022 National Survey of Indonesian Nutrition Status (SSGI) which shows a decrease in the prevalence of stunting. stunting became 21.6% from 24.4% in the previous year. In 2023, the East Java Provincial Government has achieved success, one of which is that Gresik Regency succeeded in accelerating, namely in 2021 (23.5%), in 2022 (17.6%) to 10.7% in 2023. Sedagaran is one of villages in Gresik Regency which have the title of stunting-free villages, but from the results of anemia screening it is known that the majority of young women are at risk of experiencing anaemia. This is the reason the Team carries out Community Service activities. The methods used are outreach, education, capacity strengthening and processing of local food ingredients as a solution to preventing stunting. As a result, village residents are more responsive to the symptoms of stunting, as evidenced by their preference for a healthy diet to meet nutritional needs to overcome anaemia. In conclusion, preventing stunting requires multisectoral treatment because the causes are multifactorial. The follow-up to this activity is to carry out monitoring and evaluation and recommend to the village government and health cadres to continue to promote healthy eating behaviour.